Comparison of Organic and Cultured Rainbow Trout (Oncorhynchus mykiss) Fry with Respect to Chemical Composition - YAVUZ SONMEZ, ADEM; HISAR, OLCAY; GULTEPE, NEJDET; ARAS HISAR, SUKRIYE; YANIK, TELAT (Asian Journal of Chemistry, 2010)
In present study, differences of organic fish from the cultured one was investigated with respect to moisture, crude protein, crude fat, dry matter and muscle fatty acid distribution. The experiment was carried out in 6 earthen ponds with 3 m × 2 m × 1 m dimensions at the farm in central research and extension center of agricultural faculty for 120 d in Turkey. The analysis showed that while the fish of control groups had the level average water content 81.4 ± 0.8 %, crude protein 17.6 ± 0.3 %, crude fat 1.2 % and dry ingredient 18.6 ± 0.5 %, the organically cultured fish had the averages as 80.7 ± 0.8 %, 16.8 ± 0.1 %, 0.71 % and 19.2 ± 0.3 %, respectively. Between the groups, intensively cultured fish found to have statistically higher rates of crude protein and crude fat than organically cultured fish. The differences in saturated fatty acids were not significant between fish muscle cultured intensively and organically. However, the muscle lipids of intensively cultured fish contained significantly higher percentages of linoleic acid (18:2ω6) and docosahexaenoic acid (22:6ω3) than those of the organically cultured (p < 0.01). The significantly high percentages of palmitoleic acid (16:1ω7) (p < 0.01), linolenic acid (18:3ω3) (p < 0.01) and eicasanoic acid (20:1ω9) (p < 0.05) in organically cultured fish were observed. The n-3 to n-6 fatty acid ratio was two times higher in the organically cultured fish than in the intensively cultured fish. In conclusion, fish cultured organically contain less protein, fat and more essential fatty acid than intensively cultured fish and evidently organically cultured fish are a better source of n-3 fatty acids than their intensively cultured counterparts.